FACTORS AFFECTING HOUSEHOLD INDUSTRIES IN INCREASING REVENUES - Nel Arianty (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
the purpose of this research is to make household industry industry able to compete and able to face ASEAN Economic Community and can increase family income. So to support this research, researchers make observations and observations of the household industry.